Effect of Al content on the structure of Al‐substituted goethite: a micro‐Raman spectroscopic study. (3rd October 2013) - Liu, Haibo; Chen, Tianhu; Zou, Xuehua; Qing, Chengsong; Frost, Ray L.
<x xml:space="preserve">Abstract</x> The characterization of X‐ray diffraction, X‐ray fluorescence, and field emission scanning electron microscope were used to confirm the successful preparation of Al‐substituted goethite with different Al content. The micro‐Raman spectroscopy was utilized to investigate the effect of Al content on the goethite lattice. The results show that all the feature bands of goethite shifted to high wavenumbers after the occurrence of Al substitution for Fe in the structure of goethite. The shift of wavenumber shows a good linear relationship as a function of increasing Al content especially for the band at 299 cm−1 (R2 = 0.9992). The in situ Raman spectroscopy of thermally treated goethite indicated that the Al substitution not only hinders the transformation of goethite, but also retarded the crystallization of thermally formed hematite. All the results indicated that Raman spectrum displayed an excellent performance in characterizing Al‐substituted goethite, which implied the promising application in other substituted metal oxides or hydroxides. Copyright © 2013 John Wiley & Sons, Ltd.